The Motif of Wrath and Withdrawal in Medieval European Epic and its Impact on The Homeric Question – Some Preliminary Remarks - Grossardt, Peter (Classica - Revista Brasileira de Estudos Clássicos, 2019)
Building on his research of 2009, the author of the following article will discuss some parallels to the wrath of Achilles in the medieval European tradition, especially in the Latin Song of Waltharius and in the French chanson de geste as exemplified most notably by the Geste de Fierabras. This epic forms the best parallel to the Iliad, but doesn’t seem to depend on it. It is therefore claimed that the opening of the Iliad with the immediate conflict between the king and his main vassal represents a traditional device of oral epic poetry. As a consequence, the established idea of a chronographic epic style, which has been replaced by the more dramatic Homeric poems, has to be abandoned. On the contrary, it was the dramatic and colourful motifs like the wrath of Achilles or the conquest of Troy with the help of the Wooden Horse, which formed the kernel of the legend, around which smaller episodes crystallized that were told in a more chronographic style.